2023
DOI: 10.1088/1741-4326/acc4de
|View full text |Cite
|
Sign up to set email alerts
|

The impact of fusion-born alpha particles on runaway electron dynamics in ITER disruptions

Abstract: In the event of a tokamak disruption in a D-T plasma, fusion-born alpha particles take several milliseconds longer to thermalise than the background. As the damping rates drop drastically following the several orders of magnitudes drop of temperature, Toroidal Alfvén Eigenmodes (TAEs) can be driven by alpha particles in the collapsing plasma before the onset of the current quench. We employ kinetic simulations of the alpha particle distribution and show that the TAEs can reach sufficiently strong saturation am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 91 publications
0
1
0
Order By: Relevance
“…The benign termination of the RE beam [18][19][20] is a promising candidate for a mitigation technique. Plasma waves might contribute to the avoidance of the formation of strong RE beams, as the level of magnetic perturbations [21] and Alfvénic activity in post-disruption plasmas [22,23] can have a strong influence on a subsequent runaway current formation. In the contributions by Lvovskiy et al [24,25], they present instabilities observed during disruptions in the tokamak DIII-D, which could deconfine the initial seed electrons, hence suppressing the formation of a strong RE beam.…”
Section: Introductionmentioning
confidence: 99%
“…The benign termination of the RE beam [18][19][20] is a promising candidate for a mitigation technique. Plasma waves might contribute to the avoidance of the formation of strong RE beams, as the level of magnetic perturbations [21] and Alfvénic activity in post-disruption plasmas [22,23] can have a strong influence on a subsequent runaway current formation. In the contributions by Lvovskiy et al [24,25], they present instabilities observed during disruptions in the tokamak DIII-D, which could deconfine the initial seed electrons, hence suppressing the formation of a strong RE beam.…”
Section: Introductionmentioning
confidence: 99%